Wireless multimedia sensor networks: a survey - Potdar, Vidyasagar; Sharif, Atif; Chang, Elizabeth (IEEE Computer Society, 2009)
Radio frequency identification (RFID) and Wireless Sensor Network are the two key elements of Pervasive computing. Basically RFID and sensor technologies are considered as interrelated technologies. RFID has been used in various areas including Transportation and logistic, Manufacturing and processing, Inventory and retail etc however, it lack intelligence, that is its ability to process information and respond to real world events. People are using large scale WSN to monitor real-time environment status. However WSN using IEEE 802.15.4 Wireless personal area network protocol (WPAN) or Bluetooth is complicate and costly.RFID technology, if combined with other sensors, may enable a range of other applications that can exponentially increase visibility and monitoring. Combining RFID, a general sensor can be upgraded to intelligent wireless sensor (Smart node). It will also be used for wirelessly transmitting data about its position and data from a sensor or group of sensor to a Central Control Unit (CCU)/Smart station. RFID based sensor (Smart Node) can combine sensing, computation, communication into a single small device (FPGA/DSP). Also using RFID to implement wireless communication is relatively simple and cheap too. In my present research I am implementing a new generation of Smart/Active RFID Node, with built-in sensing capabilities, capable of monitoring the environment and is also position aware and in this paper I am explaining its hardware platform.Sensor networking capabilities are urgently required for some of our most important scientific and societal problems in understanding the international carbon budget, monitoring water resources, and safeguarding public health. This is a daunting research challenge requiring distributed sensor systems operate in complex environments while providing assurance of reliable and accurate sensing.